Repair of Rectovaginal Fistulas with Martius Flap and Concomitant Levatoroplasty: A Ten-year Experience in a Tertiary Center - Adel Zeinalpour; Armin Mohammadi; Ali Reza Safarpour; Sara Shojaei-Zarghani; Seyede Saeideh Shahidinia; Seyed Vahid Hosseini (Iranian Journal of Medical Sciences)
Background: In the treatment of low- and mid-complex rectovaginal fistulas (RVF), the use of the Martius flap between the vagina and rectum following fistula repair was shown to enhance healing rates. This study reported long-term outcomes from a referral colorectal center, focusing on the use of the Martius flap for managing low- and mid-complex RVFs.Methods: This study included eligible patients who underwent Martius flap repair at Shahid Faghihi Hospital (Shiraz, Iran), between 2013 and 2023. Continence status and sexual function were assessed using the Cleveland Clinic Incontinence Score (CCIS) and the female sexual function index (FSFI) score. Fistula recurrence was defined as the postoperative passage of gas, feces, or mucosal discharge from the vagina. Statistical analyses were performed using SPSS software. Within-group comparisons were conducted using Wilcoxon signed-rank tests, and between-group analyses were performed using independent samples t tests, Mann–Whitney U tests, and Fisher’s exact tests.  P<0.05 was considered statistically significant.Results: Of the 27 cases, 37% were classified as low RVF and 63% as mid RVF. Recurrent RVF was observed in 63% of patients, with a median of 2.00 previous fistula surgeries (interquartile range [IQR]=1.50-4.50). After a median follow-up of 48 months (IQR=24.00-84.00), the total success rate was 88.9%. The CCIS significantly decreased postoperatively compared to preoperative levels (P=0.003). Postoperative FSFI scores were within an acceptable range (22.2±4.22). Conclusion: The Martius flap procedure was safe, with low morbidity and favorable functional and cosmetic outcomes. It could be considered a first-line treatment option for low- and mid-complex RVFs.